No sex-biased mortality under brood reduction during the early nestling period in the Rook Corvus frugilegus. Issue 3 (2nd July 2016) - Orłowski, G.; Kasprzykowski, Z.; Czyż, B.; Zawada, Z.
Abstract : Among birds, nestlings of the larger sex are more costly to rear. Here we test whether the mortality due to brood reduction during the early nestling period among offspring of the Rook Corvus frugilegus – a sexually dimorphic colonial breeder – is dependent on sex. We identified sex (by dissection and molecular (PCR) method), measured the tarsus length and estimated the age of 90 starved nestlings aged between 1 and 20 days old from 17 rookeries in Poland. Even though males seem to be a higher proportion (0.581) among older (> 7-day-old) nestlings, the overall sex ratio between the two sexes (44 females:46 males) did not deviate from parity, which suggests that the overall mortality among Rook offspring is balanced between both sexes. Our study implies that mortality during the early nestling period, before sexual size dimorphism becomes evident at 3 weeks old, is a potential factor limiting any sex-skewed mortality and subsequent biased sex ratios associated with size dimorphism in Rooks.